“Tilik Ndelik” Program to Increase Meaning of life and Psychological Well-being of the Elderly at the “Amanah Bunda” Social Welfare Institution, Pringsewu (Program Tilik Ndelik untuk Meningkatkan Makna Hidup dan Kesejahteraan Psikologis Lansia di Lembaga Kesejahteraan Sosial Amanah Bunda Pringsewu) - Syaifussalam, Muhammad Lathief; Qurniasih, Nila; Wilantika, Rima (Indonesia Berdaya, 2025)
Indonesia is entering a phase of aging population structure, which is marked by the proportion of the population aged 60 years and over. In 2020 it had reached 29.3 million people or 10.82% of the total population (269.9 million). Elderly people tend to experience various problems. For example, weak physical conditions such as the ability to see, hear, walk and helpless and declining health conditions so that they are susceptible to disease. Some problems that occur in the lives of the elderly due to the inability to accept change make the elderly depressed, stressed, and lonely, thus affecting the psychological well-being of the elderly. The Tilik Ndelik Program is one of inovation, that Used by researcher togetherness with LKS Amanah Bunda to the finished of the problem. The Purpose of study is to Increase Meaning of life of Life and Psychological Well-being of the Elderly at the “Amanah Bunda” Social Welfare Institution, Pringsewu. This methode that use descriptive quantitative, with pra experimental pre and post intervention design. This program have  involved 70 participant, who had  implementing of Program “Tilik Ndelik” was act in Social Welfare Institution “Amanah Bunda Pringsewu”, Intervention of the program are given Logoterapy at Eldery, who had implemented during six month, then assessment is carry out afterwards about  the Meaning of life and Psychological Well-being. This program was implemented in July-December include as preparation, training, treathening, monitoring and evaluating. The Result study show that the data obtained were then analyzed to determine the difference in significance scores before and after the training was carried out. Based on the results of the paired sample t-test, the t value = 4.222 was obtained, and the sig value = 0.000 0.05 showed that there was a very significant difference between psychological well-being before and after being given logotherapy training treatment. The Conclussion of Study prove that the influence of logotherapy for the elderly can increase the meaning of life for the elderly. Based on this study, logotherapy is very suitable to be given to clients who have feelings of meaninglessness in life.  Abstrak. Indonesia sedang memasuki fase struktur penduduk lanjut usia, yang ditandai dengan proporsi penduduk usia 60 tahun ke atas. Pada tahun 2020 telah mencapai 29,3 juta jiwa atau 10,82% dari total penduduk (269,9 juta jiwa). Lansia cenderung mengalami berbagai permasalahan. Misalnya kondisi fisik yang lemah seperti kemampuan melihat, mendengar, berjalan dan tidak berdaya serta kondisi kesehatan yang menurun sehingga mudah terserang penyakit. Beberapa permasalahan yang terjadi dalam kehidupan lansia akibat ketidakmampuan menerima perubahan membuat lansia tertekan, stres, dan kesepian, sehingga mempengaruhi kesejahteraan psikologis lansia. Program Tilik Ndelik merupakan salah satu inovasi yang digunakan peneliti bersama LKS Amanah Bunda untuk menyelesaikan permasalahan tersebut. Tujuan penelitian ini adalah untuk Meningkatkan Makna Hidup dan Kesejahteraan Psikologis Lansia di Lembaga Kesejahteraan Sosial Amanah Bunda, Pringsewu. Metode yang digunakan adalah deskriptif kuantitatif, dengan desain pra eksperimen pre dan post intervensi. Program ini melibatkan 70 peserta, yang telah melaksanakan Program Tilik Ndelik di Lembaga Kesejahteraan Sosial Amanah Bunda Pringsewu, Intervensi program ini adalah diberikan Logoterapi pada Lansia, yang dilaksanakan selama enam bulan, kemudian dilakukan asesmen tentang Makna Hidup dan Kesejahteraan Psikologis. Program ini dilaksanakan pada bulan Juli-Desember meliputi persiapan, pelatihan, perawatan, monitoring dan evaluasi. Hasil penelitian menunjukkan bahwa data yang diperoleh kemudian dianalisis untuk mengetahui perbedaan skor signifikansi sebelum dan sesudah pelatihan dilakukan. Berdasarkan hasil uji paired sample t-test diperoleh nilai t = 4,222, dan nilai sig = 0,000 0,05 menunjukkan bahwa terdapat perbedaan yang sangat signifikan antara kesejahteraan psikologis sebelum dan sesudah diberikan perlakuan pelatihan logoterapi. Kesimpulan penelitian membuktikan bahwa pengaruh logoterapi pada lansia dapat meningkatkan makna hidup pada lansia. Berdasarkan penelitian ini, logoterapi sangat cocok diberikan kepada klien yang memiliki perasaan tidak berarti dalam hidup.